Field Evaluation of Fluazinam Fungicide in Dollar Spot Populations Confirmed In Vitro Insensitivity - Shi, Xiaojing (Plant disease, 2024)
Fluazinam, a fungicide widely used in agriculture and turf management, was traditionally thought to pose a low risk of resistance. However, our in vitro sensitivity test conducted in 2021 revealed reduced sensitivity to fluazinam in dollar spot, highlighting the need for more vigilant field monitoring. In 2022 and 2023, we evaluated the field responses of four Clarireedia jacksonii isolates with varying in vitro sensitivity to fluazinam. Fluazinam was used at both a full labeled rate (0.5 oz/1,000 ft2) and a half-rate (0.25 oz/1,000 ft2) to evaluate the effectiveness in isolate-inoculated plots in the field. In 2022, both natural and sensitive isolates showed significantly better control compared to insensitive isolates under both half- and full-rate treatments. However, in 2023, half-rate fluazinam demonstrated limited control under high disease pressure, providing relative disease control of dollar spot less than 45% across all treatments. In contrast, full-rate fluazinam maintained significantly better control of natural and sensitive isolates compared with insensitive isolates. Our results, showing that in vitro insensitivity leads to field insensitivity under inoculated conditions, suggest the development of fluazinam insensitivity in the C. jacksonii population. This highlights the need for judicious use of fluazinam and the establishment of continuous resistance monitoring. Furthermore, the loss of control observed when fluazinam was applied at half-rates under high disease pressure highlights the importance of careful fungicide use